Coordination of Arctic Research in the U.S.A. - Sandved, K.G. (ARCTIC, 1969)
An Interagency Arctic Research Coordinating Committee was established in 1968, with members from the departments of Agriculture, Air Force, Army, Commerce, Health, Education and Welfare, Interior, Transportation and Navy, also the Atomic Energy Commission, National Aeronautics and Space Administration and National Science Foundation. The Committee's function is to coordinate basic, unclassified research, promote cooperative use of available logistics among research groups, maintain a current survey of foreign arctic research, and to encourage international meetings and cooperative fieldwork, data exchange and research analysis.